2013
DOI: 10.1186/1476-4598-12-156
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PMP22 mRNA by G3BP1 affects cell proliferation in breast cancer cells

Abstract: BackgroundRegulation of mRNAs is one way to control protein levels and thereby important cellular processes such as growth, invasion and apoptosis. G3BPs constitute a family of mRNA-binding proteins, shown to be overexpressed in several cancer types, including breast, colon and pancreas cancer. G3BP has been reported to both stabilize and induce degradation of specific mRNAs.ResultsHere, we show that G3BP1, but not G3BP2, supports proliferation of several breast cancer cell lines. Global gene expression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 36 publications
3
63
1
Order By: Relevance
“…Winslow et al demonstrated that PMP22 protein could regulate cell spreading and affect cell proliferation in breast cancer cells [16]. Furthermore, it has been demonstrated previously that PMP22 can interact with members of the transforming growth factor-beta (TGF-β) family [17].…”
Section: Discussionmentioning
confidence: 99%
“…Winslow et al demonstrated that PMP22 protein could regulate cell spreading and affect cell proliferation in breast cancer cells [16]. Furthermore, it has been demonstrated previously that PMP22 can interact with members of the transforming growth factor-beta (TGF-β) family [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the generation of G3BP1 knockout (KO) mice supported the role of G3BP1 in cell survival and proliferation [32]. Moreover, G3BP1 (but not G3BP2) is involved in the cellular proliferation of various breast cancer cell lines through a regulatory effect on peripheral myelin protein 22 (PMP22) [33].…”
Section: Expression Of G3bps and Their Activitymentioning
confidence: 97%
“…PMP22 is expressed primarily in neural crest derived cell lineages (including melanocytes), however expression of PMP22 has also been associated with cell proliferation and survival in breast cancer [35]. To date no target genes of miR-4731 have been functionally validated.…”
Section: Introductionmentioning
confidence: 99%